Proceedings of the 14th International Conference on Muon Spin Rotation, Relaxation and Resonance (ΜSR2017) 2018
DOI: 10.7566/jpscp.21.011042
|View full text |Cite
|
Sign up to set email alerts
|

Element Specific Imaging Using Muonic X-rays

Abstract: The RIKEN-RAL facility provides a source of negative muons that can be used to non-destructively determine the elemental composition of bulk samples. A negative muon can replace an electron in an atom and subsequently transition to lower orbital positions. As with conventional X-ray fluorescence, an X-ray photon is emitted with a characteristic energy to enable the transition between orbitals of an atom. As the mass of a negative muon is much greater than that of an electron, a higher energy X-ray photon is em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The system has been used at synchrotrons in applications which wish to discern mechanical, structural or chemical information from within thick samples or to determine the chemical composition of samples containing multiple high Z materials which, typically, have closely spaced K-line X-ray emissions. While originally developed for materials science applications [2], [3], the system has been successfully used across a diverse range of fields including pure science [4], [5], solar physics [6], medical imaging [7] and security applications [8]. This article will review the current status of the technology, the performance of the latest system and demonstrates the use of the system on a synchrotron beamline.…”
Section: Introductionmentioning
confidence: 99%
“…The system has been used at synchrotrons in applications which wish to discern mechanical, structural or chemical information from within thick samples or to determine the chemical composition of samples containing multiple high Z materials which, typically, have closely spaced K-line X-ray emissions. While originally developed for materials science applications [2], [3], the system has been successfully used across a diverse range of fields including pure science [4], [5], solar physics [6], medical imaging [7] and security applications [8]. This article will review the current status of the technology, the performance of the latest system and demonstrates the use of the system on a synchrotron beamline.…”
Section: Introductionmentioning
confidence: 99%
“…By placing a detector behind the sample, information about the spatial distribution of the sample can be obtained, especially for light elements. In Hillier et al [53] and Yabu et al [54], feasibility studies of muon imaging are reported. In both works, a highly pixelated CdTe detector is used to collect the signal (cadmium telluride is a rather good material for detection, especially in the range of hard X-rays).…”
Section: Muon Imagingmentioning
confidence: 99%
“…In both works, a highly pixelated CdTe detector is used to collect the signal (cadmium telluride is a rather good material for detection, especially in the range of hard X-rays). In [53], a proximity image (Figure 12) was obtained by placing the detector behind the sample holder and measuring it at 40 MeV/c. In [54], instead, a pinhole setup was used.…”
Section: Muon Imagingmentioning
confidence: 99%
“…Due to the high flux of muon beam enhancement in this century, 𝜇-XES element analysis has been recently applied in many fields, such as archaeological investigations [10,11], extraterrestrial material characterization [12][13][14], lithium battery development [15] and other applications [16][17][18]. Additionally, 𝜇-XES was used to study the spatial distribution of elements inside materials [19][20][21]. Hillier and collaborators placed a CdTe detector behind a sample consisting of C, Al and Fe 2 O 3 blocks to image the distribution of different elements in the sample [19].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, 𝜇-XES was used to study the spatial distribution of elements inside materials [19][20][21]. Hillier and collaborators placed a CdTe detector behind a sample consisting of C, Al and Fe 2 O 3 blocks to image the distribution of different elements in the sample [19]. Katsuragawa et al developed a pinhole camera by placing a single-hole collimator between the sample and the CdTe detector to obtain the reversed image of element distributions in the sample [20].…”
Section: Introductionmentioning
confidence: 99%